Valuing Carbone Services using Contingent Valuation Method: A case study of Mangrove Forest in the South-Western area of Madagascar - M. Rakotojaofeno; M. E. Raharison; N. L. Razafitrimo; J. L Razafindrakoto; R. R Rakotozafy (World Scientific Reports, 2023)
In more recent years, the necessity of attributing a value to nature in order to make people aware of its importance has been highlighted. The problem is therefore how to take into account and value this resource. In this context, it is necessary to take into account the fact that the wealth of a nation does not stop at its gross domestic product, but also to consider that the environment is part of its wealth and richness. Hence, the objective of this study is based on the attribution of economic value to this natural capital, including the mangroves of the south-west region of Madagascar. It is essential to make an economic evaluation to consider the environmental wealth of a territory. A contingent valuation will be carried out in this work via the evaluation of Willingness To Pay and Willingness To Receive.